PENGARUH PROMOSI PENJUALAN TERHADAP MINAT BELI PRODUK FASHION DENGAN GAYA HIDUP SEBAGAI VARIABEL MODERATOR (Survei Konsumen Pada Jejaring Sosial) - Yoebrilianti, Anggit (Universitas Serang Raya, 2018)
Fashion promotional product sales in social networks can not be ascertained the influence on consumer buying interest, as well as with the lifestyles of everyday consumers to the products offered , are able to increase or even decrease the sales promotions on buying interest .The purpose of this study was to determine the effect of sales promotions on buying interest lifestyle fashion products as a moderator variable. Promotional sales is one way to increase consumer buying interest as well as the presence of a moderator variable lifestyle can increase or decrease consumers' interest in buying fashion products through social networking.The study was conducted using quantitative methods . Quantitative method is a scientific approach to managerial decision making and economics . The goal is to present a structured overview , factual and accurate information on the facts, properties, and relationships between variables in the study and further analy statistically for later obtained a conclusion . The statistical test using t test and will partially determine whether the sales promotion through social networks influence consumer buying interest is significant or not . And with the consumptive lifestyle that consumers can have an impact on sales promotion and increasing beragaman consumers to buy.The result is a big influence for sales promotions on buying interest shown by the 50.3 % figure . Furthermore, the presence of lifestyle variables as moderator variables can increase sales promotions and buying interest at 66 % . While the influence of other variables outside the study by 34 %. From the research results obtained is sales promotion and positive influence on consumer buying interest partially through social networking . And lifestyle as a moderator variable can increase sales promotion and consumer buying interest .Keywords: Sales Promotion, Lifestyle and Interests Buy